Study of the Radio-Wave Absorbing Properties of a Lithium-Zinc Ferrite Based Composite; Russian Physics Journal; Vol. 57, iss. 5 - Surzhikov A. P. Anatoly Petrovich; Lysenko E. N. Elena Nikolaevna; Malyshev A. V. Andrei Vladimirovich; Vlasov V. A. Vitaliy Anatolievich; Suslyaev V. I.; Zhuravlev V. A.; Korovin E. Yu.; Dotsenko O. A. (2014, 2014)
Title screen